Detection of Risk Factors Causing Impaired Writing and Reading: Technological and Prognostic Aspects - Anna A.; Galina V.; Marina M.; Tatyana A.; Natalia V.; Elena D. (National Research Mordova State University, 2018)
Introduction: the relevance of the study on the diagnostics of children's preparedness for writing and reading is determined by the fact that its results contribute to identifying risk factors for the development of difficulties in literacy education. The aim of the work is to describe the results of the study of prerequisites of children's mastering of writing and reading skills and to identifydeficiency factors. Materials and Methods: theoretical (interpretative) and empirical (author's technological map) methods were used in the study. During the analytical stage of the work, a statistical processing method was used with the help of IBM SPSS Statistics Version 24 software. Results: the analysis of the materials of the experiment made it possible to establish and characterise the risk factors that cause impairment of writing and reading, reflecting the insufficient formation of oral speech, linguistic and metalanguage ability, non-verbal prerequisites for writing and reading; to allocate a group of children with sufficient (actual meaningful) level of preparedness for literacy education and children at risk. Depending on the degree and magnitude of the manifestation of risk factors, the participants in the experiment (the risk group) were divided into subgroups: children with potentially significant and children with deficient levels of preparedness for literacy education. The study reflected the effectiveness of the author's technological map, confirmed its high diagnostic and prognostic capabilities. Discussion and Conclusions: the analysed results of the research are inherently consistent with the data reflected in the works of Russian and foreign scientists. The results of this study supplement the available information and contribute to filling the gap in the study of the prerequisites for learning to write and read. The identified risk factors for the development of literacy difficulties can be used in the diagnostic and prognostic activity of teachers. Discussion of the proposed concept and obtained experimental data in the scientific and pedagogical audience reveals the real possibilities of introducing a technological map, the results of its application to the system of activity of primary school teachers and pre-school caregivers, including those involved in the implementation of inclusive education models.